Prurigo pigmentosa: a clinicopathological study and analysis of associated factors - Lu, Pei-Hsuan; Hui, Rosaline C.-Y.; Yang, Li-Cheng; Yang, Chih-Hsun; Chung, Wen-Hung (International journal of dermatology, 2011)
Background  Prurigo pigmentosa (PP), a rare inflammatory disease of the skin, is mostly reported in the ethnic Japanese population. Its pathogenesis remains unclear. The chronic and recurrent nature of PP implies a possible role of viral infection in the pathogenesis. The anti‐inflammatory mechanism of doxycycline, which is well documented as a good treatment for PP, is related to the suppression of interleukin expression. Methods  We identified and retrospectively analyzed 16 biopsy‐proven and criteria‐matched patients over a seven year period at a single medical center. DNA extracted from formalin‐fixed, paraffin‐embedded specimens was analyzed for herpes simplex virus‐1 (HSV‐1), HSV‐2, and human herpes virus‐6 (HHV‐6) DNA by polymerase chain reaction. Immunohistochemistry was performed to determine the interleukin‐6 (IL‐6) and interleukin‐8 (IL‐8) expression in PP skin lesions. Results  Clinicopathological findings in the ethnic Chinese population are similar to those reported in Japanese studies. All patients had a good response to doxycycline treatment, with a mean duration of use of 2.4 weeks. However, recurrence was noted in six patients. HSV‐1, HSV‐2, and HHV‐6 DNA in PP skin lesions were negative. Immunohistochemistry showed IL‐6 (P = 0.035) to be more strongly expressed in PP skin lesions. There was no statistical significance of elevated IL‐8 expression in PP (P = 0.123). Conclusions  Prurigo pigmentosa is not uncommon in the ethnic Chinese population. There was no evidence of herpes virus DNA in PP skin lesions. Increased expression of IL‐6 in PP skin lesions may explain the effects of doxycycline in terms of its anti‐inflammatory properties.